Selective geranylation of biflavonoids by Aspergillus terreus aromatic prenyltransferase (AtaPT). Issue 1 (20th November 2019) - Xu, Kangping; Yang, Can; Xu, Yuanyuan; Li, Dan; Bao, Shumin; Zou, Zhenxing; Kang, Fenghua; Tan, Guishan; Li, Shu-Ming; Yu, Xia
Abstract : Regio-selective geranylation of natural biflavonoids using Aspergillus terreus aromatic prenyltransferase (AtaPT) as an efficient catalyst. Abstract : Prenylation increases the bioactivity of flavonoids. Herein, we report the first examples of regioselective enzymatic geranylation of biflavonoids using Aspergillus terreus aromatic prenyltransferase (AtaPT). For biflavonoids 1–3 dimerized through a diphenyl linkage, geranylation occurs at the hydrogen bond involving C5′′–OH group, which is less chemically accessible than other OH groups in the molecule. This study would be referential for developing green synthetic solutions for prenylated biflavonoids.